An Evaluation of the Equilibrium Properties in Hexane and Ethanol Extractive Systems for Moringa oleifera Seeds and Fatty Acid Profiles of the Extracts - Karina Arguelles-Peña; José Arturo Olguín-Rojas; Andrés Antonio Acosta-Osorio; Ceferino Carrera; Gerardo F. Barbero; Miguel Ángel García-Alvarado; Guadalupe del Carmen Rodríguez-Jimenes (Separations, 2021)
Until the present, oilseed extractions have been mainly performed using hexane: a toxic, non-sustainable solvent. Extraction methods using ethanol have recently been proposed and, to evaluate the suitability of ethanol as an alternative solvent, Moringa seeds with an oil content as high as 40% have been chosen to determine the equilibrium properties in solid–liquid ethanol extractions. The equilibrium constant (Keq) and the specific retained solution (M) of the extractive systems seeds–oil–hexane and seeds–oil–ethanol were determined and validated, following a counter-current multi-stage extraction model. The extractions were carried out at 40 and 50 °C, the mass to solvent ratios used were 1:5, 1:10 and 1:20, and shelled and unshelled seeds (kernels) were tested. The Keq and M of the different kinetics revealed that Keq was not infinite in the hexane systems, whereas the ethanol systems registered slightly lower values. Regarding M, although the seed powder allowed more rapid extractions, particle size was increased to reduce M for an easier phase preparation. Finally, a counter-current multi-stage extraction system was simulated and applied under suitable conditions. The fatty acid profiles for both types of extract were similar regarding their main components. definition: